From data to decision: How the National Information Platform for Nutrition (NiPN) bridges the research-policy gap in Ethiopia's nutrition sector - Zerfu, Taddese Alemu; Samuel, Aregash (SAGE Publications, 2025)
Bridging the gap between research and policy continues to be a major challenge in Ethiopia, particularly in the nutrition sector, where evidence is often fragmented, inconsistently collected, and underutilized. Traditional research-to-policy approaches are frequently misaligned with policymaking needs due to differences in timelines, priorities, and communication practices. While these challenges are not unique to Ethiopia—and indeed, numerous global efforts have attempted to address them with varying degrees of success—examples from other settings offer useful insights for strengthening the interface between evidence and action. In the Ethiopian context, the National Information Platform for Nutrition (NiPN) represents an important shift toward a more responsive, demand-driven model that seeks to improve the relevance and uptake of evidence. Unlike conventional approaches that begin with research questions and proceed directly to data collection, Ethiopia's NiPN starts with policy question formulation, aligning evidence generation with real-time decision-making priorities. This approach emphasizes embedding research in institutional processes and tailoring outputs to policy needs. The paper explores how NiPN addresses structural barriers to nutrition governance—such as limited institutional capacity, fragmented coordination, and weak knowledge translation. It engages multiple sectors in mapping evidence, analyzing data, and supporting dialogue to inform actionable recommendations. Using examples like the Seqota Declaration and the School Feeding Programme, the paper demonstrates how NiPN has improved policy relevance, intervention targeting, and national ownership. The Ethiopian case offers transferable insights for other countries seeking to institutionalize evidence-informed policymaking in complex, multisectoral domains.